Decidindo pela vasectomia: a fala dos homens - Carneiro, Lucilla Vieira (2012)
The present study is focused on the experience of men as compared to vasectomy. This is a study of an exploratory-descriptive, developed in a health service considered the reference implementation of the vasectomy, located in João Pessoa - PB / Brazil. Presented to analyze the experience in the quest for male vasectomy, in the context of family planning. Data were obtained through interviews with 11 men attended the vasectomy program from that place of study, from June to agosto/2011 that obeying the Law No 9.263/96, showed the same chronological age less than 25 years and / or had two (02) living children. For the research was considered the precepts Resolution No 196/96 of the National Health Council on research involving humans and Resolution No. 311/2007 of the Federal Council of Nursing. Was used as a technique for analyzing the interviews, content analysis proposed by Bardin. The results verified the need for more effective performance of the Basic Health Units in relation to family planning, and increase in share offering educational group for the population, continuously, including men and all professionals in the health care team these actions. Within nursing, the contributions of this study emerge for training, whose reflections reach the best possible quality of care. It is noteworthy that the possibility of man perform vasectomy was seen by them as a conquest of their rights. It is worth recalling that, in the context of sexual and reproductive rights, with regard to contraception, the goal should always be to move towards providing people information and access to wider range of contraceptive methods, including sterilization male surgical.